A Review on Transistors in Nano Dimensions - Naif, Yasir Hashim (Penerbit Universiti Malaysia Pahang, 2015)
In this paper, a review on characterization of transistors in nano dimension for improving ICs integration was presented. Various novel device structures are being extensively explored because the conventional silicon MOSFET has scaling limits. This work was focused on fabrication technology and characterization of nanowire transistor, FinFET transistor, and carbon nanotube transistor and its applications.